Elastic modulus of low-density lipoprotein as potential indicator of its oxidation. (November 2015) - Takeda, Seiji; Subagyo, Agus; Hui, Shu-Ping; Fuda, Hirotoshi; Shrestha, Rojeet; Sueoka, Kazuhisa; Chiba, Hitoshi
Background: Evaluation of low-density lipoprotein oxidation is important in the risk assessment of cardiovascular disease. Atomic force microscope is widely used to evaluate the physical properties including stiffness on a single-particle scale. In this study, the effect of low-density lipoprotein oxidation on the low-density lipoprotein stiffness was investigated using an atomic force microscope. Methods: Isolated low-density lipoprotein particles with or without oxidation were densely bound to an Au substrate on mica, and then pressed and deformed by the atomic force microscope tip. The stiffness of each low-density lipoprotein particle was estimated as the elastic modulus obtained by the force curve analysis. Biochemical change of low-density lipoprotein due to oxidation was studied by electrophoresis. Results and conclusion: The elastic modulus of low-density lipoprotein particles ranged between 0.1 and 2 MPa. The oxidation of low-density lipoprotein increased the number of low-density lipoprotein particles with smaller elastic moduli, indicating the decrease in low-density lipoprotein stiffness. The elastic modulus of low-density lipoprotein might be potentially useful to evaluate low-density lipoprotein oxidation.